The effect of home computer use on children's cognitive and non-cognitive skills - Fiorini, M (My University, 2007)
This presentation explores whether home computer access influences the development of cognitive and non-cognitive skills in young children, using data from the kindergarten cohort of 'Growing Up in Australia: the Longitudinal Study of Australian Children' (LSAC). The presentation outlines the background and findings of the research, and features slides on the growth in household Internet and computer access, recent similar studies, the LSAC sample's access to and use of computers, models, measures used, the causal effect on pro-sociality and conduct problems, and comparisons between boys and girls. The findings indicate home computer use affects numerical skills and peer skills, particularly from weekend, non-video game use.
Keywords: Child Development; Child Development -- Cognitive; Activities; Activities -- Children's Activities; Childhood and child development; Activities; Child Development; Children's Activities; Cognitive; Childhood and child development